2017
DOI: 10.1007/s10577-017-9557-9
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal localization of Wolbachia inserts in the genomes of two subspecies of Chorthippus parallelus forming a Pyrenean hybrid zone

Abstract: Wolbachia are endosymbiotic bacteria of arthropods and nematodes that can manipulate the reproduction of various host organisms to facilitate their own maternal transmission. Moreover, Wolbachia’s presence in host germ cells may contribute to the many cases of lateral gene transfer from Wolbachia to host genomes that have been described. A previous study in Chorthippus parallelus, a well-known orthopteroid forming a hybrid zone in the Pyrenees, identified Wolbachia sequences from two major supergroups in the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 68 publications
(91 reference statements)
0
8
0
Order By: Relevance
“…Six genes of Wolbachia ( coxa, fbpa, ftsz, gatB, hcpA , and wsp ) infecting 127 Chorthippus parallelus from 21 populations inside and outside the grasshopper hybrid zone (Table 1) were sequenced following the multilocus system typing (MLST system) proposed by Baldo et al (2006b). As indicated above Wolbachia integrated sequences have been detected in C. parallelus nuclear genome (Funkhouser-Jones et al, 2015; Toribio-Fernández et al, 2017). However, different evidences rule out that they can introduce false positives in our analyses (see the Supplementary Material section for details).…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…Six genes of Wolbachia ( coxa, fbpa, ftsz, gatB, hcpA , and wsp ) infecting 127 Chorthippus parallelus from 21 populations inside and outside the grasshopper hybrid zone (Table 1) were sequenced following the multilocus system typing (MLST system) proposed by Baldo et al (2006b). As indicated above Wolbachia integrated sequences have been detected in C. parallelus nuclear genome (Funkhouser-Jones et al, 2015; Toribio-Fernández et al, 2017). However, different evidences rule out that they can introduce false positives in our analyses (see the Supplementary Material section for details).…”
Section: Resultsmentioning
confidence: 83%
“…Previous studies showed that the grasshopper subspecies diverged as a result of their geographic isolation in allopatry (Hewitt, 1993, 1999, 2001, 2011; Serrano et al, 1996) during the last glaciation. Recent cytogenetic data suggest that bacterial F strains and the ancestral C. parallelus came into contact before the hybrid zone was formed (Toribio-Fernández et al, 2017). In addition, the phylogeographical distribution of Wolbachia suggests a strong correlation between Wolbachia and its host's biogeography.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LGT of fragments of the Wolbachia genome (total size approximately 1.2 Mb), ranging from 500 base pairs to more than 1 Mb, have been observed in many invertebrates, including beetles (Nikoh et al, 2008), grasshoppers (Funkhouser-Jones, 2015;Toribio-Fernández et al, 2017), wasps (Dunning-Hotopp et al, 2007), fruit flies (Dunning-Hotopp et al, 2007;Klasson et al, 2014;Choi, Bubnell and Aquadro, 2015;Morrow et al, 2015), tsetse flies (Brelsfoard et al, 2014;Nakao et al, 2016), butterflies and moths , kissing bugs (Mesquita et al, 2015), mosquitoes (Klasson et al, 2009;Hou et al, 2014), filarial nematodes (Fenn et al, 2006;Dunning-Hotopp et al, 2007;Keroack et al, 2016) and spiders (Baldo et al, 2008).…”
Section: Uses Of Wolbachia In Control Methodsmentioning
confidence: 99%
“…LGT of fragments of the Wolbachia genome (total size approximately 1.2 Mb), ranging from 500 base pairs to more than 1 Mb, have been observed in many invertebrates, including beetles (Nikoh et al, 2008), grasshoppers (Funkhouser-Jones, 2015Toribio-Fernández et al, 2017), wasps (Dunning-Hotopp et al, 2007), fruit flies (Dunning-Hotopp et al, 2007;Klasson et al, 2014;Choi, Bubnell and Aquadro, 2015;Morrow et al, 2015), tsetse flies (Brelsfoard et al, 2014;Nakao et al, 2016), butterflies and moths (Ahmed et al, 2016), kissing bugs (Mesquita et al, 2015), mosquitoes (Klasson et al, 2009;Hou et al, 2014), filarial nematodes (Fenn et al, 2006;Dunning-Hotopp et al, 2007;Keroack et al, 2016) and spiders (Baldo et al, 2008).…”
Section: Uses Of Wolbachia In Control Methodsmentioning
confidence: 99%